Transverse Vibrations of Clamped and Simply-Supported Circular Plates with Two Dimensional Thickness Variation - N. Bhardwaj; A.P. Gupta; K.K. Choong; C.M. Wang; Hiroshi Ohmori (Shock and Vibration)
Two dimensional boundary characteristic orthonormal polynomials are used in the Ritz method for the vibration analysis of clamped and simply-supported circular plates of varying thickness. The thickness variation in the radial direction is linear whereas in the circumferential direction the thickness varies according to cos kθ, where k is an integer. In order to verify the validity, convergence and accuracy of the results, comparison studies are made against existing results for the special case of linearly tapered thickness plates. Variations in frequencies for the first six normal modes of vibration and mode shapes for various taper parameters are presented.